PENERAPAN PEMBELAJARAN BERDIFERENSIASI TERHADAP PENINGKATAN HASIL BELAJAR PESERTA DIDIK KELAS V MATA PELAJARAN MATEMATIKA DI SDN DUPAK 1 SURABAYA - Nur Alfiana Safitri; Roni Rodiyana; Dwi Natalia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the effect of implementing a differentiated learning approach on the improvement of learning outcomes for fifth-grade students in mathematics. This research is motivated by the significant variation in students' learning abilities, which impacts the disparity in learning outcomes in the classroom. The research method used is Classroom Action Research (CAR) conducted in two cycles, where each cycle consists of the stages of planning, action implementation, observation, and reflection. This research was conducted at SDN DUPAK 1 Surabaya with the research subjects being the fifth-grade class V-D, which consists of 33 students. The data analysis technique used in this research is quantitative descriptive analysis. The results of the research through differentiated learning show that there is an improvement in student learning outcomes as seen from the pre-cycle activities, where the completeness of student learning outcomes increased from 36% to 58% in cycle I. Then, in cycle II, it increased to 85% in terms of student learning outcomes. The results of this study indicate that implementing differentiated learning can improve student learning outcomes in mathematics on the topics of LCM and GCF for fifth grade at SDN DUPAK 1 Surabaya.